(untitled) - SarDesai, D. R. (New Delhi, 1977)
This book the author presents a new interpretation of the events leading to the Opium War, which has been a subject of much controversy among hitorians.
Keywords: Imperialism,Great Britain,Chủ nghĩa đế quốc,Vương quốc Anh; Colonies,Thuộc địa; Asia,Châu Á